Association between Addiction of Social Media and Depression among Medical Students - Samia Sarwar, Muhammad Amin Khan, Naeem Amjad, Qurratulain Mehfooz, Farrukh Sarrfraz, Zain Gulzar (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: This study examined the association between addiction of social media and depression among medical students. Social Media is the online administrations where individuals can communicate with each other by distinctive ways like enjoying, commenting and sharing are collectively known as social media. Depression is one of the major mental wellbeing issues around the world, particularly among youthful adults. According to World Health Organization (WHO), more than 264 million individuals suffer from depression. Depression can cause the severe issues in people to suffer significantly in their way of life and it basically affects their every day schedule activities such as studying, working and family chores, though the extreme level of misery can lead to suicide. Around 800 000 individuals commit suicide each year and suicide is identified as the moment leading cause of death among teen agers. Objective: To investigate the association between addiction of social media and depression among medical student Material and Methods Study design: Quantitative cross sectional Settings: Rawalpindi Medical University Duration: Six months i.e. 1st April 2022 to 30th July 2022 Data Collection procedure: A pre validated questionnaire was used. Total numbers of participants were 150. Addiction of social media was measured utilizing Dr Kimberly Young’s Web Habit Test (IAT). Depression was calculated by the Middle for Epidemiologic Studies Depression Scale (CES-D) which was established by Lenore Radloff. Results: Total numbers of students 150 who were participated after taking the informed consent and use regular platform of social media and subscribed. Males were 110 and females 40. Internal consistency was perfect. Cronbach’ Alpha value was more than .82 in both depression and addiction of social media. Mean and standard deviation was calculated. The values of skewness and kurtosis were also calculated Conclusion: this study uncovers that social media compulsion has a positive relationship with depression among students. In other words, the higher the student addiction level, and the more prominent his/her sadness level is. Keywords: Social Media, Depression, Students, Addiction